The ‘Societal Turn’. Historicising Future Society - Beeckaert, Esther; Berghmans, Sander; Bruneel, Dieter; Cottyn, Hanne; De Reu, Pieter; Schepers, Marjolein; Vandamme, Tobit; Van Melkebeke, Sven (TSEG - The Low Countries Journal of Social and Economic History, 2018)
As a group of young historians we are strongly convinced that the future of social and economic history will be a collective endeavour that crosses institutional and disciplinary boundaries. Only by means of continuous and intensive interaction junior researchers will be able to bring the societal turn to a decisive phase in the next ten years. This turn represents an upsurge of social and economic history that is deeply embedded in and engaged with public challenges and debates by means of conscious participation and dissemination of historical analyses. Particularly, the societal turn will involve research that brings to the forefront three interrelated research perspectives: inequality, ecology and connectivity. For these are the three lenses through which socio-economic historians of the coming decades will produce new scientific knowledge that is centred around ongoing societal processes. In the following essay, we collectively take up our responsibility in historicising future society.